Investigating the invisible roots of a prevailing narrative of farmers' failed collective action in Morocco. Issue 3 (3rd May 2020) - Bouzidi, Zhour; Faysse, Nicolas; Kuper, Marcel; Billaud, Jean-Paul
ABSTRACT: In rural areas in developing countries, the origin and persistence of prevailing narratives of failed collective action have often been explained by the existence of relations of domination. This article focuses on a case in which power relations alone cannot explain the persistence of a prevailing narrative. In a large-scale irrigation scheme in Morocco, farmers and staff from the regional agricultural development authority share the view that farmers lack the capacity to undertake successful collective action. This narrative influences public policies as well as the farmers' self-esteem. It prevails despite rare communication between the farmers and the staff of the development authority and despite several successful examples of informal collective action at local scale. An analysis of the different actors' discourses and of the farmers' practices revealed the different underlying root causes of the narrative: (i) farmers and development authority staff overlook contextual factors, (ii) they confuse collective action with formal farmers' organisations, (iii) the resistance of words where the actors describe a changed situation using the same words, and (iv) the nostalgia of the older generation for a strong state-managed scheme. As a consequence, actors consider that the failure of past collective action is the farmers' fault, irrespective of the unfavourable context and the legacy of the past. Studies of prevailing narratives that are not simply linked to power relationships, should go beyond discourse analysis and focus on actors' practices and on the origin of the narratives. Understanding the roots of prevailing narratives can also help challenging them.